Spectroscopic Quantitative Measurement of the Cartilage Surface using Arthroscopy Correlates with a Conventional Macroscopic Grading System - Shizuka Sasaki, M.D; Eiji Sasaki, M.D; Yuji Yamamoto, M.D; Yuka Kimura, M.D; Daisuke Chiba, M.D; Takahiro Tsushima, M.D; Eiichi Tsuda, M.D; Yasuyuki Ishibashi, M.D (Elsevier, 2023)
Purpose: To quantify the cartilage surface profile visualized during arthroscopic surgery and examine its clinical utility by comparing the results of quantitative measurements with a conventional grading system. Methods: Fifty consecutive patients diagnosed with knee osteoarthritis and who underwent arthroscopic surgery were included in this study. A 4 K camera system was used, and the cartilage surface profile was visualized using the augmented reality imaging program. The highlighted image was displayed in 2 colors: black (the worn cartilage area) and green (the part where the cartilage thickness was maintained). The percentage of the green area was calculated using ImageJ and used as an index of cartilage degeneration. The quantitative value was statistically compared with the International Cartilage Repair Society (ICRS) grade as a conventional macroscopic evaluation. Results: In the quantitative measurement, the median percentage of the green area was 60.7 at ICRS grades 0 and 1 (interquartile range [IQR], 67.3-51.0), 47.2 at grade 2 (IQR, 54.1-39.2), 36.5 at grade 3 (IQR, 43.2-30.4), and 34.0 at grade 4 (IQR, 38.5-29.3). There was a significant difference between the macroscopic grades, except for Grades 3 and 4. There was a significant negative correlation between macroscopic evaluation and quantitative measurement (r = −0.672, P < .001). Conclusions: The quantitative measurement of the cartilage surface profile using the spectroscopic absorption technique was significantly correlated with the conventional macroscopic grading system and demonstrated fair to good inter-rater and intra-rater reliabilities. Level of Evidence: Level II, diagnostic (prospective cohort study).